A Prospective Evaluation of the Acute Effects of High Altitude on Cognitive and Physiological Functions in Lowlanders - Falla, Marika; Papagno, Costanza; Dal Cappello, Tomas; Vögele, Anna; Hüfner, Katharina; Kim, Jenny; Weiss, Elisabeth M.; Weber, Bernhard; Palma, Martin; Mrakic-Sposta, Simona; Brugger, Hermann; Strapazzon, Giacomo (Frontiers in Physiology, 2021)
Cognitive function impairment due to high altitude exposure has been reported with some contradictory results regarding the possible selective cognitive domain involvement. We prospectively evaluated in 36 lowlanders, exposed for three consecutive days to an altitude of 3269 m, specific cognitive abilities (attention, processing speed, decision making) required to safely explore the mountains, as well as to work at altitude. We simultaneously monitored also the physiological parameters. Our study provides evidence of a reduced processing speed in lowlanders when exposed to altitude in the first 24 hours. There was a fairly quick recovery since it was no more detectable after 36 hours of exposure. There were no clinically relevant effects on decision making, while psychomotor vigilance was unaffected at altitude except for individuals with poor sleep. Significant changes were seen in physiological parameters (increased heart rate and reduced peripheral oxygen saturation). Our results may have practical implication suggesting that individuals should practice prudence with higher ascent when perform risky activities, even at altitudes below 3500 m, in the first 24-36 hours due to an impairment of the cognitive performance that could worsen and lead to accidents.